PEMBUKTIAN SIFAT RUANG BANACH PADA B1/4(K) - Malahayati Malahayati (EPSILON: JURNAL MATEMATIKA MURNI DAN TERAPAN, 2013)
In this paper we study class of bounded Baire-1=4 functions on a separablemetric space K denoted by B1=4(K). Haydon, et all [5] proved that B1=4(K) is a Banachspace by using the series criterion for completeness. In this paper we prove the statementin a dierent way.